Prognostic significance of residual functional SYNTAX score II in acute myocardial infarction - Xinjun Lin; Zhendong Cheng; Wei Ji; Zhibin Mei; Yaoguo Wang; Chaoxiang Xu (PLoS ONE, 2026)
Background The residual functional SYNTAX (Synergy Between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery) score (rFSS) predicts patient prognosis post-percutaneous coronary intervention (PCI). We aimed to integrate rFSS with clinical risk factors (rFSS-II) to comprehensively assess patient prognosis, guided by the quantitative flow ratio (QFR), and compare its predictive efficacy with other scoring systems. Methods We enrolled 175 acute myocardial infarction (AMI) patients undergoing post-PCI physiological measurements. Three distinct models were established based on different calculation methods of rFSS-II, and their respective abilities to predict major adverse cardiac events (MACE) were evaluated. Patients were categorized into high rFSS-II (n = 70) and low rFSS-II (n = 105) groups. The MACE incidence was compared between these groups over a 3-year follow-up period, using multivariable Cox regression analysis to identify MACE predictors. Results High rFSS-II patients had more MACE than low rFSS-II patients (55.7% vs. 18.1%; p < 0.001). The rFSS-II model had higher accuracy than other traditional risk scores, except for rSS-II. In a multivariable-adjusted model, rFSS-II emerged as an independent predictor of MACE (adjusted hazard ratio: 1.08 per 1 unit increase, 95% confidence interval [CI]: 1.05–1.11, p < 0.001). Conclusions QFR-guided rFSS-II proved to have good predictive value among AMI patients 3 years post-PCI. Calculating the total score of all vascular segments with QFR ≤ 0.80 may provide enhanced predictive capability.